2020
DOI: 10.1002/ppul.25037
|View full text |Cite
|
Sign up to set email alerts
|

Area under the curve achievement of once daily tobramycin in children with cystic fibrosis during clinical care

Abstract: Background The area under the concentration‐time curve over 24 hours (AUC24) is frequently utilized to monitor tobramycin exposure in children with cystic fibrosis (CF). An understanding of exposure target achievement during clinical implementation of an AUC24 based approach in children is limited. Methods A retrospective chart review was performed in children with CF treated with once daily tobramycin and drug concentration monitoring at a pediatric CF center. During clinical care AUC24 was estimated using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…In a retrospective study of 77 children with CF treated with once daily tobramycin at a mean dose of 12.5 mg/kg/day, Brockmeyer et al found that 52% met the AUC 24 target of 80-120 mg*h/L after the initial dose based on log-linear regression. 13 This is comparable to our analyses, in which 43-44% of simulated patients given 12-13 mg/kg/day met this AUC target with log-linear regression. Brockmeyer also utilized Bayesian forecasting, based on a two-compartment model, to estimate AUC 24 for each subject.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In a retrospective study of 77 children with CF treated with once daily tobramycin at a mean dose of 12.5 mg/kg/day, Brockmeyer et al found that 52% met the AUC 24 target of 80-120 mg*h/L after the initial dose based on log-linear regression. 13 This is comparable to our analyses, in which 43-44% of simulated patients given 12-13 mg/kg/day met this AUC target with log-linear regression. Brockmeyer also utilized Bayesian forecasting, based on a two-compartment model, to estimate AUC 24 for each subject.…”
Section: Discussionsupporting
confidence: 85%
“…Brockmeyer also utilized Bayesian forecasting, based on a two-compartment model, to estimate AUC 24 for each subject. 13 Again, similar to our assessment, estimates of AUC 24 using Bayesian methods were higher than with log-linear regression (mean difference of 6.4 mg*h/L). 13 These findings have significant clinical ramifications.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…To optimize dosing, pharmacokinetics play an important role. A retrospective review of once‐daily tobramycin dosing studied the usage of 24 h AUC (AUC 24 ) and the feasibility of various predictive pharmacokinetic models 69 . Using the traditional narrow (vs. broad) target AUC 24 was remarked to be challenging, as multiple lab draws are required with the unclear clinical difference between the two.…”
Section: Introductionmentioning
confidence: 99%